2004
DOI: 10.1080/1355260042000261760
|View full text |Cite
|
Sign up to set email alerts
|

Community-based treatment of sex offenders

Abstract: What treatment is available to sex offenders in the community, and why is it important to treat them? This paper focuses upon the treatment provided by the Probation Service as well as issues surrounding the development and progression of this treatment over recent years. The prevalence and incidence of sexual abuse are discussed, as are the characteristics of sex offenders. In addition, this paper provides a detailed account of some of the most recent theories of treatment and assessment, and the impact that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In addition, the treatment progress of the child molesters was not assessed, and it is possible the molesters would have demonstrated an even greater degree of distortions on the CMS prior to receiving treatment. Nonetheless, current results support the notion that cognitive distortions of sex offenders tend to persist and should be continually monitored, regardless if offenders are participating in or have completed treatment or are in jail (Langevin et al, 2004;Mandeville-Norden & Beech, 2004;Wood & Riggs, 2008). Items of the CMS also include post hoc excuses to sexual crimes, suggesting that treatment providers might find this instrument useful in assessing dynamic risk factors.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, the treatment progress of the child molesters was not assessed, and it is possible the molesters would have demonstrated an even greater degree of distortions on the CMS prior to receiving treatment. Nonetheless, current results support the notion that cognitive distortions of sex offenders tend to persist and should be continually monitored, regardless if offenders are participating in or have completed treatment or are in jail (Langevin et al, 2004;Mandeville-Norden & Beech, 2004;Wood & Riggs, 2008). Items of the CMS also include post hoc excuses to sexual crimes, suggesting that treatment providers might find this instrument useful in assessing dynamic risk factors.…”
Section: Discussionsupporting
confidence: 68%
“…R esearchers have attempted to classify sex offenders in an effort to better understand this form of offending behavior, and to identify whether there are different types of sex offenders, within the main groups of child molesters, rapists, and so on (e.g., Marshall, 1997), and the implications this has for treatment (Mandeville-Norden & Beech, 2004). Blackburn (1993) identified specific methods of classification that could be employed for general offenders, and Bickley and Beech (2001) later applied this approach to the classification of child molesters.…”
mentioning
confidence: 99%
“…The answers have been mixed, although meta-analyses have demonstrated that offenders who successfully complete cognitive-behavioral or relapse prevention modification treatment protocols tend to fail (recidivate) less often and fail (recidivate) less quickly than their nontreated counterparts (Alexander, 1999; Aos, Phipps, Barnoski, & Lieb, 2001; G. Hall, 1995; Hanson et al, 2002; Lösel & Schmucker, 2005; Mandeville-Norden & Beech, 2004). This does not mean, however, that the efficacy of sex offender treatment is a foregone conclusion (Rice & Harris, 2003; Seto et al, 2008).…”
Section: Risk Factors For Sex Crimesmentioning
confidence: 99%